Death Profiling of Hospitalized Patients with COVID-19: Experience from a Specialized Hospital in Bangladesh - Morshed, Md Shahed; Mosabbir, Abdullah Al; Hossain, Mohammad Sorowar (Bangladesh Journal of Microbiology, 2022)
The information on characteristics and causes of mortality in deceased patients with coronavirus disease 2019 (COVID-19) is scarce in the literature. This study is aimed to document the clinical profile with causes of death in deceased patients admitted to a COVID-19 dedicated hospital in Dhaka, Bangladesh. This cross-sectional retrospective study included 108 RT-PCR confirmed COVID-19 associated deceased patients admitted in Kurmitola general hospital, Dhaka, Bangladesh, between 25 March 2020 and 24 June 2020) Data were collected from hospital records. Causes of death were categorized into early-death and late-death, with a cut-off of 48 hours of hospitalization. Among 809 hospitalized cases of COVID-19, 108 patients died (13.35%) over three months of the study period. The median age of the deceased patients was 60.0 (50.0, 70.0) years; 86.1% were male. About 85% had at least one comorbidity with diabetes mellitus (65.7%) was the most common one. The most common symptoms were breathlessness (88.0%), fever (65.7%) and cough (43.5%). Nearly 75% presented with severe disease. Patients had altered biochemical profiles and were treated with different drugs, including antibiotics and steroids. Young age and undernutrition were two characteristic features. Only one-third got intensive care support. The most common cause of death was acute respiratory distress syndrome (95.37%). Septic shock and acute myocardial infarction were predominant among early death cases, and uremia, hepatic failure, and hyperglycemic crisis were the predominant causes of late hospital death. The findings of this study will help clinicians and policymakers to take the necessary steps to prevent deaths from COVID-19 in the Bangladeshi population. Bangladesh J Microbiol, Volume 38, Number 2, December 2021, pp 45-49